Causes of relapse and search for treatment reported by drug users in a rehabilitation unit (Colombia Medica, 2024)
Objectives: To identify the causes of relapse and search for treatment by drug users.Methodology: This was a qualitative exploratory research carried out in an Addiction Rehabilitation Unit at a psychiatric hospital in Paraná State, Brazil. Data were collected from May to June 2010 through a semistructured interview with 12 drug addicts. They were further analyzed and organized into thematic categories.Results: Five categories emerged from the analysis: Environment influences relapse; Non-recognition of the powerlessness facing addiction; Difficulty in coping with frustrations; Inaction fosters cravings for psychoactive substances; Losses, co-morbidities, and recognition of powerlessness lead to the search for treatment.Discussion: Among the motivations for relapse, external influences related to the social context, as well as internal ones such as difficulties with self-perception were pointed out. The subjects attributed to losses, several aspects of their lives and the recognition of the control deficit over the addiction as the ultimate factors to search for treatment.Conclusion: It can be concluded that those subjects’ recovery is favored by the conjunction of physical, emotional, and social factors. Thus, it is deemed necessary that health professionals continuously refine their knowledge on this theme to be qualified to deliver thorough care to these clients.